Tanytarsini (Diptera: Chironomidae) from madicolous habitat in Southeast Brazil: new species and new records - Trivinho-Strixino, Susana; Shimabukuro, Erika Mayumi (Zootaxa, 2017)
Tanytarsini (Diptera: Chironomidae: Chironominae) collected from madicolous habitats in Brazil are analyzed, and three new species of Tanytarsus van der Wulp are described and illustrated: T. angelae sp. n. and T. alaidae sp. n. as adult male and T. alienus sp. n. as male and female. New records of another Brazilian Tanytarsus species are also presented, and immature stages of Paratanytarsus silentii Trivinho-Strixino are described.